Penggunaan Media Crossword Puzzle terhadap Penguasaan Kosakata Bahasa Arab - Putri, Zelikha Annisa; Muthmainnah, Sitti; Saleh, Nurming (Universitas Negeri Makassar, 2024)
Abstract. This research is a Quasi Experimental research with a Nonequivalent Control Group Design. The purpose of this study is to determine the effectiveness of the use of Crosswod Puzzle media in vocabulary mastery (mufradat) in grade VII students of MTsS Sheikh Yusuf Gowa. The independent variable in this study is the use of Crossword Puzzle media and the bound variable is vocabulary mastery (mufradat). The population in this study is grade VII students consisting of 2 classes. The samples in this study are students of class VII A as an experimental class with a total of 26 students and class VII B as a control class with a total of 22 students with a sampling technique using Total Sampling. The data from this study was obtained by providing pre-test and post-test. The average score of students obtained from the control class after doing the post-test was 64.09 and the average score obtained from the experimental class after doing the post-test was 85.58. So that between the control class and the experimental class, after the results of the calculation of the hypothesis test at a significant level of 0.05, a significant value of 0.001 < 0.05 was obtained, which showed that the use of Crossword Puzzle media was effective on the mastery of Arabic vocabulary (mufradat) of grade VII MTsS students Sheikh Yusuf Gowa.Keywords: Effectiveness, Crossword Puzzle media, vocabulary mastery (mufradat)